Radiation Synthesis of High-Temperature Wide-Bandgap Ceramics; Micromachines; Vol. 14, iss. 12 - Lisitsyn V. M. Viktor Mikhailovich; Tulegenova A. T. Aida Tulegenkyzy; Golkovsky M. G. Mikhail Gedalievich; Polisadova E. F. Elena Fyodorovna; Lisitsyna L. A. Lyudmila Aleksandrovna; Musakhanov D. A. Dosymkhan Abitkhanovich; Alpysova G. K. Gulnur Kenzhebekovna (2023, 2023)
Title screen